Intracellular fusion of sequentially formed endocytic compartments (The Rockefeller University Press, 1988)
A polyclonal anti-fluorescein antibody (AFA) which quenches fluorescein fluorescence has been used to distinguish between two models of intracellular vesicle traffic. These models address the question of whether sequentially endocytosed probes will mix intracellularly or whether they are carried through the cell in a sequential, isolated manner. Using transferrin (Tf) as a recycling receptor marker, we incubated Chinese hamster ovary (CHO) cells with fluorescein-Tf (F-Tf) which is rapidly endocytosed. After the F-Tf was completely cleared from the surface, AFA was added to the incubation medium and entered endocytic compartments by fluid phase endocytosis. Fusion of a vesicle containing AFA with the compartment containing F-Tf results in binding of AFA to fluorescein and the quenching of fluorescein fluorescence. When AFA was added to the culture medium 2 min after clearance of F-Tf from the surface, time dependent fluorescence quenching occurred. After 20 min, 67% saturation of F-Tf with AFA was observed. When the interval between F-Tf clearance and AFA addition was increased to 5 min only 41% saturation of F-Tf was found. These data indicate that there are some compartments which are accessible for mixing with subsequently endocytosed molecules, but the efficiency of mixing falls off rapidly as the interval between pulses is increased. In CHO cells Tf swiftly segregates to a collection of vesicles or tubules in the para-Golgi region, and at steady state most of the F-Tf is in this compartment. Using digital image analysis to quantify quenching in this region, we have found that F-Tf/AFA mixing is occurring either within this compartment or before transferrin enters it.